Six-Phase Fully Coreless Axial-Flux Permanent-Magnet Generator: Design, Fabrication, and Performance Analysis - Turki M. Alsuwian; Asiful Habib; Muhammad Ammirrul Atiqi Mohd Zainuri; Ahmad Asrul Ibrahim; Nasrudin Abd Rahim; Adam R. H. Alhawari; Abdulkarem H. M. Almawgani; Saleh Almasabi; A. T. Hindi; Mohamed Fauzi Packeer Mohamed (IEEE Access)
Coreless axial-flux permanent-magnet (AFPM) machines have recently gained prominence as efficient power generation solutions. Eliminating the core resolves challenges such as eddy current losses and cogging torque, enhancing overall efficiency. This topology enables high power density, further amplified in fully coreless configurations. Nevertheless, the proliferation of coreless AFPM machines faces hurdles as to high leakage flux and weaker structural integrity. Additionally, adopting multi-phase setups in AFPM introduces challenges, requiring additional winding coils and enlarging the stator diameter, leading to bulkier machine designs. This article underscores the significance of a lightweight, fully coreless six-phase machine and proposes a modular, multi-stage, multi-phase design tailored for fault-tolerant small-scale power generation applications. Furthermore, it explores the impact of employing double-layer winding coils on air-gap-flux density and power output. To realize this aim, a six-phase multi-stage AFPM generator was designed and simulated using ANSYS Maxwell. Subsequently, a laboratory-scale prototype was fabricated accordingly. The simulation findings closely align with the experimental results obtained from the prototype, demonstrating the achievement of 1.3 kW power output. Notably, the six-phase machine with fully coreless concept exhibits a substantial power density of 205 W/kg. Multi-stage design boost efficiency and power density, presenting potential for small-scale applications.